A New Algorithm for Post-Processing Covering Arrays - Lara-Alvarez, Carlos; Avila-George, Himer (International journal of advanced computer science & applications, 2015)
Software testing is a critical component of modern software development. For this reason, it has been one of the most active research topics for several years, resulting in many different algorithms, methodologies and tools. Combinatorial testing is one of the most important testing strategies. The test generation problem for combinatorial testing can be modeled as constructing a matrix which has certain properties, typically this matrix is a covering array. The construction of covering arrays with the fewest rows remains a challenging problem. This paper proposes a post-processing technique that repeatedly adjusts the covering array in an attempt to reduce its number of rows. In the experiment, 85 covering arrays, created by a state-of-the-art algorithm, were subject to the reduction process. The results report a reduction in the size of 28 covering arrays (~33%).